The continuity of multilinear integral operators on Morrey spaces - Liu, Lanzhe (Annales Mathematicae Silesianae, 2022)
In this paper, the continuity of some multilinear integral operators on Morrey spaces are obtained. The operators contain singular integral operators, Littlewood-Paley operators, Marcinkiewicz operators and Bochner-Riesz operators.